Recent advances and challenges in the interaction between myofibrillar proteins and flavor substances - Qian, Rong; Sun, Chang; Bai, Ting; Yan, Jing; Cheng, Jie; Zhang, Jiamin (Frontiers in Nutrition, 2024)
Myofibrillar proteins are an important component of proteins. Flavor characteristics are the key attributes of food quality. The ability of proteins to bind flavor is one of their most fundamental functional properties. The dynamic balance of release and retention of volatile flavor compounds in protein-containing systems largely affects the sensory quality and consumer acceptability of foods. At present, research on flavor mainly focuses on the formation mechanism of flavor components, while there are few reports on the release and perception of flavor components. This review introduces the composition and structure of myofibrillar proteins, the classification of flavor substances, the physical binding and chemical adsorption of myofibrillar proteins and volatile flavor substances, as well as clarifies the regulation law of flavor substances from the viewpoint of endogenous flavor characteristics and exogenous environment factors, to provide a theoretical reference for the flavor regulation of meat products.